The Evolution of Islam in Sri Lanka: A Study of History, Practices and Islamic Da’wah (Propagation) Strategies, 19th-21st Centuries - Wijaya, Iqra Pandu; Erasiah, Erasiah; Hakim, Lukmanul (Tarikhuna: Journal of History and History Education, 2024)
Sri Lanka is a country with a long history and geographically strategic, located in the shipping route of east-west. This made Sri Lanka a meeting point between various religions and cultures. Islam was first intrododuced in Sri Lanka by Arabic merchants. As time passed, Muslims from different countries started to arrived, including the Moor, Malay as well as Muslims from India and Pakistan. Themethod used in this research is library research by using sources from books, journals, seminar proceedings, research report, websites, etc. The approach of social knowledge is used in this research. The result of this research is the history of the arrival of Islam in Sri Lanka and its ddevelopment and the strategy of Muslims in Sri Lanka in doing Da’wa using various methods suitable to today’s development of globalisation era.